Understanding the psychological drivers of sustainable purchasing behavior: a study of The Body Shop customers in Padang city - Ridwan Ridwan; Gesit Thabrani (Universitas Negeri Padang, 2023)
Objective study this is for study influence factors psychological behavior purchase to behavior sustainable purchases to consumers of The Body Shop in Padang City. Population study this is a consumer ever buy product from The Body Shop. A total of 200 respondents chosen as sample research and data collected through charging questionnaire online. Data processing is done use device SmartPLS software. Research results show that (1) encouragement For responsible answer to environment own influence positive and significant to behavior sustainable purchase (2 ) perception effectiveness consumer influential positive and significant to behavior sustainable purchase (3 ) attitude to sustainable purchase _ own influence positive and significant to behavior sustainable purchase _ (4) Consumers Knowledge Regarding Sustainability Related no own influence towards Sustainable Purchase Behavior (5) Spirituality own influence towards Sustainable Purchase Behavior